ECONOMETRIC MODELING OF TOURISM INDICATORS IN THE REGION (International Conference on Scientific Research in Natural and Social Sciences, 2025)
The article will cover the methods of analyzing the main indicators of the regional tourism sector and their econometric modeling. Economic factors of Tourism Development and their relationship are studied. With the help of econometric models, ways are shown to forecast and improve the efficiency of the growth rates of the tourism industry.